Accounting for light source angular distribution in backscattering Mueller matrix interpretation using double-planar small-angle scattering trajectory approximation. (February 2022) - Wang, Zhen; Gao, Haiyang
Highlights: Double-planar small-angle scattering approximation is extended to account for light source angular distribution. Lidar Mueller matrix is formulated by introducing azimuthal angle of emitting light relative to meridian plane of receiving direction. Azimuthal angle of emitting light can significantly adjust the linear relation between normalized Mueller matrix and backscattering phase matrix. The validation was done by the Monte Carlo simulations for inclined pencil-like source, ring-shaped source and Gaussian divergent source. Abstract: We extend the double-planar small-angle scattering trajectory approximation to account for the influence of the light source angular distribution on the polarization patterns of lidar backscattering returns from highly forward-peaked scattering medium. We formulate the lidar Mueller matrix return by introducing the azimuthal angle of emitting light relative to the meridian plane of receiving direction. The derived formulas have exactly the same forms as that for the vertical pencil-like light source. The essential difference is that the azimuthal angle of the emitting light can adjust the linear relation between the normalized Mueller matrix and single backscattering phase matrix as the dihedral angle between the outgoing and return forward scattering plane does too. The emitting azimuth effect can be significantly stronger than the effect of the dihedral angle of the two forward scattering planes when the receiving directions are within the cone of divergence. It can make the normalized elements of the Mueller matrix being zeros except those diagonal elements describing the linear and circular polarization degrees.